2013
DOI: 10.1093/nar/gkt861
|View full text |Cite
|
Sign up to set email alerts
|

DNA intermediates of meiotic recombination in synchronous S. pombe at optimal temperature

Abstract: Crossovers formed by recombination between homologous chromosomes are important for proper homolog segregation during meiosis and for generation of genetic diversity. Optimal molecular analysis of DNA intermediates of recombination requires synchronous cultures. We previously described a mutant, pat1-as2, of the fission yeast Schizosaccharomyces pombe that undergoes synchronous meiosis at 25°C when an ATP analog is added to the culture. Here, we compare recombination intermediates in pat1-as2 at 25°C with thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…This is similar to average focus counts for Rec7-GFP and Rad51 in a previous study (Lorenz et al 2006), and is in line with an estimated~60 DSB events/nucleus/ meiosis (Fowler et al 2014) considering that single-DSB events might cluster together (Fowler et al 2018). Previously, temperature-induced changes in physical DSB formation at an ade6 hotspot allele have been observed in a unisexual and artificially synchronized meiotic system using mutant pat1 alleles, with DSB frequency being notably lower at 25°C than at 34°C (Hyppa et al 2014). These discrepancies can have several technical sources, such as higher synchrony in meiotic cultures of pat1 strains (Loidl and Lorenz 2009), and the unisexuality of the pat1 synchronization tool affecting various meiotic processes (Bähler et al 1991;Chikashige et al 2004;Hyppa and Smith 2010;Hyppa et al 2014) resulting in different readouts compared with normal zygotic or azygotic meiosis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is similar to average focus counts for Rec7-GFP and Rad51 in a previous study (Lorenz et al 2006), and is in line with an estimated~60 DSB events/nucleus/ meiosis (Fowler et al 2014) considering that single-DSB events might cluster together (Fowler et al 2018). Previously, temperature-induced changes in physical DSB formation at an ade6 hotspot allele have been observed in a unisexual and artificially synchronized meiotic system using mutant pat1 alleles, with DSB frequency being notably lower at 25°C than at 34°C (Hyppa et al 2014). These discrepancies can have several technical sources, such as higher synchrony in meiotic cultures of pat1 strains (Loidl and Lorenz 2009), and the unisexuality of the pat1 synchronization tool affecting various meiotic processes (Bähler et al 1991;Chikashige et al 2004;Hyppa and Smith 2010;Hyppa et al 2014) resulting in different readouts compared with normal zygotic or azygotic meiosis.…”
Section: Discussionsupporting
confidence: 90%
“…pombe, but that gene conversion, especially at hotspots engendered by point mutants in ade6, is cold-sensitive. Further experimentation indicates that in addition to changes in the formation of DSBs (Hyppa et al 2014), DSB processing could be another source for a reduced gene conversion frequency particularly at temperatures below 25°C.…”
Section: Introductionmentioning
confidence: 99%
“…. Previous studies of genome-wide DSBs showed similar DSB profiles at both 34°C and 25°C (Hyppa et al, 2014); however, several DSB hotspots were found only at 34°C or at 25°C, indicating temperature may change the LinE binding pattern at certain loci. Determining the difference between the two LinE configurations and understanding the regulatory mechanism of the configuration change will likely shed light on the role of LinEs in DSB interference and DSB repair.…”
Section: Discussionmentioning
confidence: 73%
“…LinEs gather nearby clusters into a visible dotty focus, which may expand to fill the chromosomal gaps between the foci and become the linear structure. In addition, LinEs likely remain on the chromosome after the DSBs are made and until MI (Figures 2, 3D, and S7;Hyppa et al, 2014). This proposal raises the possibility that LinEs also participate in other meiotic processes, such as DSB repair, including chromosomal partner choice for DSB repair.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation